TOPICAL APPLICATION OF ELADI TAILA AND GHRITAKUMARI IN PESTICIDE- INDUCED CUTANEOUS TOXICITY - Arsude, Rahul; Kadam, Ruta; Choudhary, Dimple (International Journal of Ayurveda and Pharma Research, 2015)
The vast and liberal use of pesticides in agriculture has resulted in occurrence of cutaneous toxicity; produced by the irritating chemical substances, is one of the most noticeable effects of exposure to chemicals, prominently by cutaneous, oral or inhalation routes. Thus arises the need to identify a topical remedy to prevent, reduce or nullify them. Open Randomized Clinical Trial was conducted and selected patients were randomly allotted into two groups, Control and Trial. The control group consisted of 10 patients whereas the trial group was further subdivided into 3 groups of 10 patients each. Thus, the total sample size of the study was 40, calculated on the basis of rate of incidence of the condition.Patients of the Group A did not receive any trial drug but followed symptomatic treatment as and when required. Patients of Group T1 were made to apply Ghritakumari prior to commencement of pesticidal spraying. Patients of Group T2 were not subjected to pre spraying application of Ghritakumari but post spraying Eladi taila was applied after decontamination. Patients of Group T3 were advised to follow both pre and post spraying regimens of groups T1 and T2 and were continued daily upto 2 days after the end of the complete spraying procedure with daily follow up. The primary end point of the present study was achieved and the results were found to be statistically significant.